SPLINTING OF IMPLANT WITH ACRYLIC RESIN TO MINIMIZE THE GAP BETWEEN IMPLANT ABUTMENT AND S UPERSTRUCTURE - , Sularsih ([Yogyakarta] : Fak.Kedokteran Gigi Universitas Gadjah Mada, 2012)
Background. The passive fit of superstructure is importance for successful implant treatment. Splinting implant with acrylicresin may decrease the distorsion and improve impression accuracy. Purpose. The purpose of this study was to investigate and compare the gap between implant abutment and superstructure: splinting and unsplinting of implant impression technique, in innovative in vitro experiments. Materials and methods. Impressioncopingwere connected with auto-curingresin (Acrylicresin for pattern, GC, Japan) of about 2 mm in thickness around four analog implant for splinting in master cast. After that, the splinting between implant analog was cut off to release deformation and new pattern resin was applied on the surface of cut section. The working cast was taken with splinting technique (group 1) and unsplinting technique (group 2). The gap between implant abutment and superstructure at one screw test was evaluated with a digital microscope system (VH- Z100 &amp